The Dynamic Relationship of Stock Indexes on Interbank Money Market Rates: Evidence from Thailand - Wang, Zongjun; Gongkhonkwa, Rujira (International Journal of Economics and Financial Issues, 2013)
Many researches shed light on investigation the several variables that might be able to influence economic system, this research play an important to identify the relationship of stock indexes on interbank money market rates, we make used of a secondary data by based upon the top ten largest stock exchanges in the world and BIBOR from 2006 to 2011 and applied the simple linear regression model as our model. Over the whole sample period, the result that we have found from the variance decomposition analysis and impulse response analysis there are three important stock indexes which lead up to the BIBOR changes that consists of DJIA, FTSE100, and ASX. Another interesting feature found in this study is that from the Granger causality analysis, the DJIA, NASDAQ, NIKKEI225, FTSE100, TSX, SSE, BOVESPA, ASX, and DAX were found to directly causality on the BIBOR, except the HSI over the sample period. Keywords: Interbank money market; Bangkok Interbank Offered Rate; Stock indexes JEL Classifications: G01; G21; G32